UHF RFID technologies for identification and traceability - Laheurte, Jean-Marc (ISTE, 2014)
Annotation
Includes bibliographical references and index. - Print version record
Keywords: Radio frequency identification systems; Systèmes d'identification par radiofréquence; TECHNOLOGY & ENGINEERING; Mechanical